Stratified analysis of carotid plaque and intima–media thickness as stroke predictors in type 2 diabetes - Fu, Hongmei; Wei, Xianwen; Wirtz, Stefan (Frontiers in Endocrinology, 2025)
BackgroundStroke represents a common macrovascular complication among individuals with type 2 diabetes (T2DM). Carotid intima-media thickness (IMT) and carotid plaque (CP) serve as key indicators of cerebrovascular pathology. However, it is still unclear whether the associations of IMT and CP with stroke vary across different diabetic patient subgroups. We aimed to investigate the associations of IMT and CP with stroke in T2DM patients and further explored the subgroup variations.MethodsIn this cross-sectional study, 2,627 T2DM patients aged 32–80 years were enrolled. Baseline data including age, sex, anthropometrics, blood pressure, lipid profiles, smoking status, and medication use were collected. IMT and CP were measured by ultrasonography. Logistic regression analysis was used to evaluate their associations with stroke. Stratified and interaction analyses were performed to assess subgroup-specific variations.ResultsAmong 2,627 enrolled participants, 51.8% reported CP, 17.8% had increased IMT (>=0.9mm), and 7.8% reported history of stroke. Multivariate analysis demonstrated that IMT and CP were differentially associated with risk for stroke. After adjustment for confounding variables, CP showed stronger associations with stroke (OR = 2.97, 95% CI: 2.04-4.33) compared to IMT. Stratified analyses showed that: (1) IMT had stronger associations with stroke in females (OR = 2.33), older patients (≥60 years) and diabetes duration >10 years; (2) CP showed stronger associations with stroke in males (OR = 3.44), younger patients (≤49 years), and patients with diabetes duration <5 years; (3) CP showed stronger association in smokers, while IMT had higher association with stroke in non-smokers.ConclusionBoth of the two vascular markers IMT and CP showed associations with stroke in T2DM patients; however, there were significant subgroup variations. Individualized risk assessment in diabetic patients may have important clinical implications. All these findings warranted further prospective studies to confirm the subgroup-specific associations and establish causality.